Breeding and biotechnology approaches to enhance the nutritional quality of rapeseed byproducts for sustainable alternative protein sources- a critical review - Manikandan, Anandhavalli; Muthusamy, Saraladevi; Wang, Eu Sheng; Ivarson, Emelie; Manickam, Sudha; Sivakami, Rajeswari; Narayanan, Manikanda Boopathi; Zhu, Li-Hua; Rajasekaran, Ravikesavan; Kanagarajan, Selvaraju (Frontiers in Plant Science, 2024)
Global protein consumption is increasing exponentially, which requires efficient identification of potential, healthy, and simple protein sources to fulfill the demands. The existing sources of animal proteins are high in fat and low in fiber composition, which might cause serious health risks when consumed regularly. Moreover, protein production from animal sources can negatively affect the environment, as it often requires more energy and natural resources and contributes to greenhouse gas emissions. Thus, finding alternative plant-based protein sources becomes indispensable. Rapeseed is an important oilseed crop and the world's third leading oil source. Rapeseed byproducts, such as meals or cakes, are considered the best alternative protein source after soybean owing to their promising protein profile (30-60% crude protein) to supplement dietary requirements. After oil extraction, these rapeseed byproducts can be utilized as food for human consumption and animal feed.However, anti-nutritional factors (ANFs) like glucosinolates, phytic acid, sinapine, and tannins make them unsuitable for direct consumption. Techniques like microbial fermentation, advanced breeding, and genome editing can improve protein quality, reduce ANFs in rapeseed byproducts, and facilitate their usage in the food and feed industry. This review summarizes these approaches and offers the best bio-nutrition breakthroughs to develop nutrient-rich rapeseed byproducts as plant-based protein sources.